Feature-oriented development of applications for a domain - Kang, K.C. (Proceedings. Fifth International Conference on Software Reuse (Cat. No.98TB100203), 1998)
Software reuse is generally considered by both practitioners and researchers as one of the most effective ways of increasing productivity and improving quality of software. To achieve successful software reuse, commonalities of related systems must be discovered and represented in a form that can be exploited in developing similar systems. FORM (Feature-Oriented Reuse Method) (K.C. Kang et al., 1998), extended from the FODA (Feature-Oriented Domain Analysis) method (K.C. Kang et al., 1990), is a systematic method that focuses on capturing commonalities and differences of applications in a domain in terms of "features" and using the analysis results to develop domain architectures and components. Once a domain is described and explained in terms of common and different "units" of computation, they are used to construct different "feasible" configurations of reusable architectures. Features are distinctively identifiable functional implemented, tested, delivered, and maintained. Therefore, they are the first class objects in the development of domain oriented software.